2013
DOI: 10.1039/c3lc50798j
|View full text |Cite
|
Sign up to set email alerts
|

A CMOS wireless biomolecular sensing system-on-chip based on polysilicon nanowire technology

Abstract: As developments of modern societies, an on-field and personalized diagnosis has become important for disease prevention and proper treatment. To address this need, in this work, a polysilicon nanowire (poly-Si NW) based biosensor system-on-chip (bio-SSoC) is designed and fabricated by a 0.35 μm 2-Poly-4-Metal (2P4M) complementary metal-oxide-semiconductor (CMOS) process provided by a commercialized semiconductor foundry. Because of the advantages of CMOS system-on-chip (SoC) technologies, the poly-Si NW biosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…As such, cantileverbased fully integrated CMOS DNA diagnosis system-on-chip can be used to perform label-free DNA detection with high sensitivity. CMOS DNA cantilever sensor was embedded with a physical transducer of a polysilicon piezoresistor [74]. These compact, inexpensive, and high stability systems are known as a CMOS BioMicro electromechanical systems (CMOS Bio-MEMS) platform.…”
Section: Cmos Sensor Array As Electronic Chip For Label-free Dna Detementioning
confidence: 99%
“…As such, cantileverbased fully integrated CMOS DNA diagnosis system-on-chip can be used to perform label-free DNA detection with high sensitivity. CMOS DNA cantilever sensor was embedded with a physical transducer of a polysilicon piezoresistor [74]. These compact, inexpensive, and high stability systems are known as a CMOS BioMicro electromechanical systems (CMOS Bio-MEMS) platform.…”
Section: Cmos Sensor Array As Electronic Chip For Label-free Dna Detementioning
confidence: 99%
“…In order to replace traditional optical inspection techniques, these techniques have been tested for the identification of objects at microscopic level to envision several applications [2].…”
Section: Introductionmentioning
confidence: 99%
“…127 Immunoamperometric techniques, using a commercial kit, were used to validate the accuracy of novel technology for virus concentration determination. 127 Huang et al 128 reported a polysilicon nanowire-based biosensor system-on-chip, fabricated by complementary metal-oxidesemiconductor (CMOS) process. In addition, an on-off key wireless transceiver was also integrated to form a wireless biosensor system-on-chip technology.…”
mentioning
confidence: 99%
“…In addition, an on-off key wireless transceiver was also integrated to form a wireless biosensor system-on-chip technology. 128 This was a pioneering work to harness the momentum of CMOS-integrated technology into emerging biodiagnosis technologies, and examined to have label-free and low-concentration biomolecular detection, as a consequence. Such developed technology can be a promising candidate for on-field and personalized applications in biomedical diagnosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation